The sequence of RNA segment 1 of influenza virus A/NT/60/68 and its comparison with the corresponding segment of strains A/PR/8/34 and A/WSN/33. - Jones, K L (1983)
The complete nucleotide sequence of RNA segment 1 of influenza virus A/NT/60/68, corresponding to the PB2 protein, has been determined. It is 2341 nucleotides long, encoding a predicted product of 759 amino acids with a net charge of +27 1/2 at neutral pH. The predicted amino acid sequence has been compared to the equivalent sequences in influenza viruses A/PR/8/34 and A/WSN/33. Evolutionary divergence, assuming a direct lineage from A/PR/8/34 and allowing for "laboratory drift", is 0.08% per year. The alignment of RNA segment 10 of A/NT/60/68 with segments 1 and 3 is completed, confirming that it is a mosaic of regions from these two segments.